A Monograph on Theoretical Understanding of the Contradictions of Vested Interests and Underdevelopment in Peripheral Social Formation - Ogbonna, Hyginus Obinna (Richtmann Publishing, 2021)
This paper focuses on theoretical understanding of the contradictions of vested interests and the underdevelopment in the peripheral social formations; having as its raison d'être, to explore the possible ways by which the vested interests of a particular social group or class has contributed in shaping the underdevelopment of the periphery in the global economy –with inferences from a sub-Saharan African country, Nigeria (with empirical-based evidences); and moving forward, to find ways to counteract or mitigate these contradictions for the amelioration of the human condition in the periphery. Thus, the paper achieves its objectives by adopting a qualitative descriptive method of analysis, investigating the contradictions of the vested interests of both the neo-colonial elite in the Periphery and the capitalists of the Center (advanced capitalist nations), with an admixture of